Estimation of the magnitude of soil and sediment erosion in the Yaraa Valley Basin using the - Al-Muardhi, Ass.Pro PhD Hussein Joban Oreibi (Thi Qar Arts Journal, 2022)
The Yaraa Valley Basin is part of the Hamrin Hills extending as a strip surrounding the sedimentary plain from the east, parallel to the Zagros Mountains and the Tonel Mountains in Iranian lands. The upper sources of the basin are those extending in Iranian lands, which receive more than 370 mm of rain annually from the humid climate that supplies the basin with water, In addition, the slope of more than 25 degrees, as well as the various geological formations, contributed to the nature of soil erosion in this basin. The aim of this research was to estimate the size of erosion and sediments transferred towards the mouth of the valley, as well as to find appropriate solutions to limit soil deterioration in this aspect. Geographical information and remote sensing in order to apply the equations of the EPM model, and the results extracted from the application of this model showed that the most important factors affecting the intensity of erosion depend on the topographical factor and the lithological factor as well as the change in land use, While the coefficient of Z for potential erosion was about 0.2-1.5, and the volume of erosion in the valley was about 63% of the total basin area, and this confirms that most of the basin area is exposed to severe erosion according to the EPM model.